Evaluation of physical euthanasia for neonatal piglets on-farm - Dalla Costa, Filipe Antonio [UNESP]; Gibson, Troy J.; Oliveira, Steffan Edward Octávio [UNESP]; Gregory, Neville George; Coldebella, Arlei; Faucitano, Luigi; Ludtke, Charli Beatriz; Buss, Liziè Peréirã; Dalla Costa, Osmar Antonio (Oxford University Press (OUP), 2020)
Twenty-seven neonate piglets (range from 0.35 to 1.17 kg) were evaluated for the effectiveness of blunt force trauma as a method of on-farm cull. Brainstem function, brain injury, and hemorrhage scores (increasing from 0 to 3) were assessed after striking the head against a concrete floor. Electroencephalograms (EEG) from a subset of 15 piglets were recorded before and after blunt force trauma for electrophysiological assessments. Blunt force trauma was performed by a single experienced farmer in a commercial farm by holding the piglet by its both hind legs and striking the head against the concrete floor. All piglets remained recumbent and did not show brainstem reflexes. Only one piglet did not presented tonic/clonic physical activity. The mean time to the onset of persistent isoelectric EEG was 64.3 ± 7.3 s (range 18 to 115). Total power, theta, alpha, and beta power decreased to approximately 45%, 30%, 20%, and 15% from pretreatment power, respectively, by 15-s post-impact. There were no periods of normal-like EEG after the culling. Bruises in the neck and shoulder were found in 67% and 70% of piglets, respectively. All piglets presented skull fractures with 20% having the nasal bone(s) fractured. Brain damage was found in all piglets, mainly in the frontal lobe(s). The occipital lobe(s) presented the greatest frequency of severe damage. The analysis of the radiographs also found a high frequency of fractures in this region. Hemorrhage was most frequent in the frontal, parietal, occipital lobes, and midbrain. When performed correctly with the appropriate weight class, blunt force trauma can be used as an effective method for the on-farm killing of nursing piglets resulting in death. However, this method should not be promoted over more reliable and repeatable cull methods such as captive bolt gun. As with blunt force trauma, there is a significant potential for animal welfare harm associated with inappropriate practice, lack of accuracy, issues with repeatability, and operator fatigue.
Keywords: animal welfare; brain injury; culling; electroencephalogram; killing; piglet